Approximating Exogenous Variation in R&D: Evidence from the Kentucky and North Carolina SBIR State Match Programs - Lanahan, Lauren; Feldman, Maryann P. (The Review of Economics and Statistics, 2018)
This paper exploits policy discontinuities at U.S. state borders to examine the effect of R&D investments on innovative projects. We examine the Small Business Innovation Research (SBIR) State Match program, which offers noncompetitive grants to federally awarded SBIR Phase I projects that are eligible to compete for Phase II. Results from SBIR activity (2002–2010) indicate heterogeneous treatment effects. Notably, the positive differential effects are moderated by firms within the science and health fields and with less previous SBIR success. The State Match effectively stabilized Phase II trends in contrast to neighboring states that experienced greater declines from the concurrent recession.